Learning Destinations : The complexity of tourism development - Gibson, Laila (Fakulteten för samhälls- och livsvetenskaper, 2006)
Our world is becoming increasingly complex, and is rapidly changingwith distances being reduced. Societies today are also in atransition from traditional production industries to increasingreliance on communication, consumption, services and experience. Asone of these emerging ‘new industries’, tourism is part of thismovement. Globalisation also makes further development of tourismpossible through, amongst other things, the spreading of languages;the development of low-cost carriers; international monetary systems;telecommunications and other technological innovations. Tourismcontributes to the globalisation of society and at the same time is aproduct of it. This is confirmed by complexity theories that stressthe systematic and dynamic nature of globalisation and theinterdependence of the global and the local. Hence, in this thesis,it is argued that acknowledging the complexity of tourism isnecessary for understanding tourism development, and more knowledgeabout tourism also leads to greater knowledge of our society. The main aim of this thesis is to understand the complexity of localand regional tourist destination development, by exploring social andcultural factors that influence this development. In order to fulfilthis aim, analysis has been conducted at three different levels:places, projects and people. More specifically, by examining placesand how they develop as destinations; investigating the structure of,and processes within, groups and networks important for destinationdevelopment and by exploring the roles, resources and attitudes ofenterprising people who are seen as key for development. The thesisis based on a research project including three studies of tourismdestinations and projects in Northern Sweden and Scotland. The social and cultural factors connected to tourism development arein turn part of learning processes, which in this thesis are seen asfundamental mechanisms for processes of development. A frameworkcalled ‘Learning Destinations’ is introduced that demonstrates howimportant social ...